Effect of temperature variation on shift and broadening of exciton band in Cs₃Bi₂I₉ layered crystals - Machulin, V.F.; Motsnyi, F.V.; Peresh, E.Yu.; Smolanka, O.M.; Svechnikov, G.S. (Физика низких температур, 2004)
The exciton reflection spectra of Cs₃Bi₂I₉ layered crystals is investigated in the temperature region
4.2–300 K with light polarization E ⊥ c. It is estimated that the energy gap Eg equals
2.857 eV (T = 4.2 K) and the exciton binding energy Ry is 279 meV. A nontraditional temperature
shift of Eg(T) for the layered substances is found for the first time. It is learned that this shift is
described very well by the Varshni formula. A transition region in the temperature broadening of
the half-width H(T) of the exciton band with the increase of temperature is registered in the interval
between 150 and 220 K. It is shown that this region may be identified as the heterophase structure
region where ferroelastic and paraelastic phases coexist. A surge of H(T) at the point of the
ferroelastic phase transition (Tc = 220 K) is also observed.